PEMBINAAN GARAP SABET DISANGGAR PEDALANGAN SERENGAN SURAKARTA UNTUK MENINGKATKAN KUALITAS GARAP PAKELIRAN - Suwondo Suwondo (Institut Seni Indonesia Surakarta, 2016)
The learning condition in studio pedalangan Serengan which is not yet systematically arranged needs some improvements. The activity aims to give knowledge and/or practice of pedalangan to the audience in studio pedalangan Serengan especially garap catur. The material given is sabet lakon Gathotkaca Sungging presented by Ki Nartasabda which is edited by Purbo Asmoro. The method used in learning of pakeliran practice in studio pedalangan Serengan is appreciation, giving speech, and demonstration. Based on the method, students are able to master material sabet well. The materials include sabet of the characters: Duryudana, Baladewa, Durna, Karna, Sengkuni, Nilayaksa, Kartamarma, Jayadrata, Gathotkaca, Samba, Setyaki, Antareja, Dewapawaka, Abimanyu, Semar, Gareng, Petruk, Bagong, Pragalba, Anoman, Arjuna, Banowati, Lesmanawati, and Bhatara Guru. Besides that, other materials are also given covering sabet jejer kahyangan dan Ngastina, sabet adegan babak unjal, sabet bedhol jejer, sabet budhakan, sabet jaranan, sabet perang ampyak, sabet budhalan buta, sabet abur-aburan gathotkaca, sabet Werkudara mlumpat, and sabet abur-aburan Kresna and Janaka.Key words: studio, pedalangan, sabet, puppet